Combining land cover, animal behavior, and master plan regulations to assess landscape permeability for birds - Bhakti, Tulaci; Pena, João Carlos [UNESP]; Niebuhr, Bernardo Brandão [UNESP]; Sampaio, Juliana; Goulart, Fernando Figueiredo; Azevedo, Cristiano Schetini de; Ribeiro, Milton Cezar [UNESP]; Antonini, Yasmine (My University, 2021)
Cities are new and expanding ecosystems that harbor a variety of habitats with different degrees of permeability to the local fauna. However, the assessment of urban landscape permeability usually considers biotic and abiotic conditions, with sociopolitical dimensions (e.g., zoning regulations) – also important in shaping urban biodiversity – being underrepresented in the formulation of resistance surfaces. Our main goal was to compare urban landscape permeability for birds between two scenarios: one that considers only species’ responses to land cover for the formulation of resistance surfaces (LandC), and another that incorporates how birds would respond to different levels of occupation (i.e., amount of permeable area and maximum building height per individual lot) given the urban zoning regulations defined by the city's master plan (LandC + UrbZ). We used the software LSCorridors to simulate Multiple Least Cost Corridors (MLCC) for five forest bird species. We hypothesized that incorporating master plan regulations would better describe the variation on landscape resistance through the urban landscape. The simulations resulted in different MLCC among species and between scenarios, highlighted by differences in landscape permeability. As expected, simulations for scenario LandC resulted in more options for straighter paths than simulations for scenario LandC + UrbZ. Our results demonstrate the potential influences of sociopolitical aspects on landscape permeability modelling. Within cities, species movements are influenced not only by behavioral and environmental characteristics, but also by the urban landscape that was shaped by planning and management decisions throughout a city's history. Therefore, we emphasize that sociopolitical dimensions must be considered when assessing urban landscape permeability.
Keywords: Functional connectivity; South American city; Understory birds; Urban ecology; Urban planning